Pembuatan Biodiesel Dari Minyak Kelapa Dengan Katalis H-Zeolit Melalui Proses Metanolisis - Feni Nopriza; Syaiful Bahri; Yusnimar Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel is an alternative fuel from renewable raw materials. One of the raw material can be used to make biodiesel is coconut oil. This research aims is determine the maximum biodiesel yield by using varying amounts of H-zeolite catalyst and methanol mole ratios of coconut oil through a process methanolysis. The independent variables used in this study is the mole ratio of methanol-oil 3: 1; 6: 1; 8: 1 9: 1 and catalyst concentration of 1%, 2%, 3% respectively. Temperature of 60°C, 1.5 hours and stirrer speed is keep constant. The yield of biodiesel produced in this study reached 84.78% at a concentration of 2% catalyst mole ratio of methanol-oil 6: 1. The density of biodieselproduced at the maximum yield was 880.90 kg / m3, kinematic viscosity of 4.59 mm2 / s, the flashpoint of 110oC, the water content of 0.048% v, and the acid number of 0.65 mg KOH / g, respectively in addition, analysis of the chemical compositions of biodiesel is used GC - MS. All the characteristics of the physical properties of biodiesel produced have met the standard range contained in the SNI 04-7182-2006.Keywords: biodiesel, homogeneous catalysts, methanolyisis, coconut oil.